Development Of New Analytical Methods Involving Novel Sorbents And Membranes For The Determination Of Selected Mycotoxins And Related Metabolites In Biological Fluids And Food - Lee, Tien Ping (2013)
This thesis focuses on the development and validation of new sample preparation methods applied to the determination of mycotoxins and their related substances. Additionally, a high performance liquid chromatography (HPLC) method for the determination of sphinganine (Sa) and sphingosine (So) in urine samples by employing a silica based monolithic column is described. Under the optimized conditions, separation was achieved using a mixture of methanol:water (93:7, v/v), column temperature at 30°C, flow rate of 1 mL min-1 and injection volume of 10 μL. A marked reduction in separation time (less than 6 min) was found compared to approximately 14 min by using a conventional C18 particle column. Twenty two urine samples from the healthy donors and seven samples from the liver cancer patients were analyzed using the method. Molecularly imprinted polymers (MIPs) for citrinin (CTN) were prepared with 1-hydroxy-2-naphthoic acid (HNA) and 1- naphthol (NA) as mimic template. Hybrid MIP membrane were next prepared by embedding the NA-MIP particles into the polyethersulfone scaffold using phase inversion technique. The resultant membranes were evaluated for the extraction of CTN and were determined using HPLC with fluorescence detection.